A smart solution for preventing environmental pollution caused by overflowing onsite sewage septic tank. Issue 4 (April 2023) - Oduah, Uzoma Ifeanyi; Ogunye, Emmanuel B.
Abstract: An innovative remote sensing device for the detection and monitoring of sewage levels in underground onsite septic tank is developed. The overflow of underground onsite sewage septic tanks located around buildings for the collection and disposal of wastewater is hazardous to the environment releasing infectious pollutants and obnoxious contaminants. The inability to accurately determine the level of the sewage in the underground septic tank most times causes overflow of sewage into the environment without the knowledge of the users of the facility. A smart onsite sewage septic tank level monitoring device is developed enabling the users of the facility to promptly detect when it malfunctions to plan ahead for the evacuation in order to prevent the overflow. The device implements ultrasonic sensor to detect and monitor level of the wastewater in the septic tank and a Global System for Mobile Communications (GSM) module to send short message service (SMS) to the enrolled users' mobile phone numbers and the sewage evacuation agents. A test run conducted showed response time within 30 s. The developed device is suitable for low income countries of Africa. Highlights: Remote sensing of On-Site sewage septic tank levels is introduced. The developed device uses ultrasonic sensor technology for detection of sewage levels. The data on septic tank levels is transmitted online via GSM module to the enrolled evacuation agents. The efficacy of the developed device was validated through field test on sewage septic tank. Developed device is low cost, uses solar power, and is suitable for Africa.